MENGINTEGRASIKAN PENALARAN DAN PENDEKATAN ILMIAH DALAM PEMAHAMAN AGAMA: Telaah Dialektika Term Rasional dan Scientific - Muhammad Sirojuddin; Iksan Kamil Sahri; Abdul Majid; Dawi Farah Adibah (IAIN Pontianak, 2023)
Studying Islam is not enough just by studying it in bits and pieces. Islam can also be used as a scientific study with a note that it is studied in a completely and comprehensively appropriate approach or way. One approach that can be used in studying and understanding Islam is a rational-scientific approach. In this qualitative research, the author uses a literature review by taking from various reference sources that focus on discussing Islamic Studies from a rational and scientific point of view. The findings of this research believe that the rational point of view supports the function of reason in reasoning and helps solve existing problems. Likewise with the scientific point of view which is a positive integration between different perspectives, none other than the two perspectives above can benefit Islam's turn as a religion that contains values, teachings, principles, norms of life that are humane. and universal can be understood properly and correctly. The spirit to think is also supported by the teachings of Islam itself. This can be seen how the various styles of Al-Qur'an language to describe thinking activities and not monotonous. According to Ian Barbour, there are four approaches to conflict, independence, dialogue and integration. The method used is divided into four stages, namely observing a phenomenon, formulating tentative explanations, further observing and experimenting, refining and retesting explanations.